Characteristics Of Spiritual and Social Values in Saman Dance Culture In Gayo Community - Hardi Alunaza; Mentari Mentari (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
This research is going to explain the characteristics of spiritual and social values in saman dance culture in gayo community in Aceh. Saman Gayo dance is not only unique but also has original Indonesian cultural values which is one of the media for delivering da'wah messages which contains religious values, manners, togetherness, and educational values. This research on the characteristics of spiritual and social values in the Saman Dance culture in the Gayo community is a descriptive study with a qualitative approach. The data analysis technique in this paper refers to the data analysis technique of Miles and Huberman with three stages, namely data collection, data processing, and drawing conclusions. The data collection technique in this paper is to use data collection methods that are literature study to more accurately research from a scientific perspective. The results of this paper shown that the Gayo Saman Dance has various philosophies such as singing, movement, types of Saman Dance, to its function which of course must be maintained and preserved. In the other hand, Saman Dance is used to strengthen Local Identity, good values ranging from values in the field of education, unity and integrity, friendship.